Integração de imigrantes: desenvolvimento e implementação de um sistema de apoio à decisão - Emília Malcata Rebelo (2009)
In this article are presented the framework, goals, results and conclusions of the research project Urban Planning for Immigrant Integration. A methodological approach is proposed, and an integrated and interactive decision-support system is developed applied to the Oporto Metropolitan Area that accounts for the characterization of the patterns of residential land use by different groups of immigrants, and anticipates the location of new incomers, and respective evolution. Considering regional development strategies, this system suports the definition of policies that improve immigrantsŽ welcome and socio-economic and professional integration, that may translate either through the provision of housing, infrastructures, equipments and jobs, or through the development of governance devices, within a sustainable environment.